2022
DOI: 10.1177/08853282221139274
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor AA-modified electrospun fibers promote tendon healing

Abstract: Platelet-derived growth factor AA (PDGF-AA) is an important promoter of tissue injury repair and might be a candidate for improving the mechanical properties of repaired tendons. Here, we designed a PDGF-AA-modified poly(lactide-co-glycolide) acid (PLGA) electrospun fibers to promote tendon rehabilitation after injury. In the present study, we grafted PDGF-AA on the surface of PLGA. In structural experiments, we found that the hydrophilicity of PLGA containing PDGF-AA (PLGA-PDGF-AA) increased, but the strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Kang et al suggested that the long-term local PDGF delivery by porous microspheres modified with heparin has a great potential to enhance tendon healing in a rat model of Achilles tendinitis by suppressing inflammation responses ( Kang et al, 2019 ). PDGF-AA-modified poly (lactide-co-glycolide) acid (PLGA) electrospun fibers (PLGA-PDGF-AA) effectively promoted tendon healing by stimulating collagen synthesis, deposition, and mechanical strength of tendon tissue ( Wang et al, 2022 ). The sustained delivery of PDGF-BB via an electrospun DegraPol tube to the wound site in a full-transection rabbit AT model accelerated tendon wound healing by causing a more uniform cell distribution, with higher proteoglycan content and less fibrotic tissue ( Meier Burgisser et al, 2020 ).…”
Section: Gfs In At Injurymentioning
confidence: 99%
“…Kang et al suggested that the long-term local PDGF delivery by porous microspheres modified with heparin has a great potential to enhance tendon healing in a rat model of Achilles tendinitis by suppressing inflammation responses ( Kang et al, 2019 ). PDGF-AA-modified poly (lactide-co-glycolide) acid (PLGA) electrospun fibers (PLGA-PDGF-AA) effectively promoted tendon healing by stimulating collagen synthesis, deposition, and mechanical strength of tendon tissue ( Wang et al, 2022 ). The sustained delivery of PDGF-BB via an electrospun DegraPol tube to the wound site in a full-transection rabbit AT model accelerated tendon wound healing by causing a more uniform cell distribution, with higher proteoglycan content and less fibrotic tissue ( Meier Burgisser et al, 2020 ).…”
Section: Gfs In At Injurymentioning
confidence: 99%
“…The results showed hrEGF causes an increase in healing tissue at the levels of neovascular, tendon cells, fibroblasts, collagen, and tissue macrophages, and higher levels of TNF-α, IL-6, IL8, and CXCR2 [ 52 ]. Wang et al [ 53 ] found that platelet-derived growth factor AA-modified electrospun fiber (PLGA-PDGF-AA) effectively promoted tendon healing, and in summary, PLGA-PDGF-AA promoted regeneration after tendon-bone injury. PLGA-PDGF-AA is a potential adjunct to the repair of surgical tendon injuries.…”
Section: Growth Factorsmentioning
confidence: 99%